Exploring the singularity of human neurons: keep calm and carry on - Libé-Philippot, Baptiste (Frontiers in Synaptic Neuroscience, 2025)
The human brain’s increased cognitive abilities are underpinned by evolutionary adaptations at the molecular, cellular, and circuit levels of neural structures. This perspective explores how protracted neuronal development and divergent cell intrinsic neuronal properties, including neuronal excitability, contribute to human neurobiological singularity. Those cellular aspects rely on molecular evolutionary innovations, including evolution of gene regulation and gene duplications that play critical roles in prolonging synaptogenesis and reducing neuronal excitability. These molecular evolutionary innovations are shown to interact with core neurodevelopmental molecular pathways linked to neurodevelopmental disorders. Furthermore, complementary multimodal and multiscale approaches offer promising platforms to study these processes and develop species-relevant therapeutic strategies. They include ex vivo acute brain slices and organotypic cultures which offer emerging tools for understanding human species-specificities and neural disorders.